Assessment of In-Vitro Antioxidant Potential of Ethyl Acetate Fraction of Hydroalcoholic Extract of Aerva Javanica Linn. Flowering Tops - Khunteta, Alok; Swarnkar, Surendra K; Gupta, Manish Kumar; Swarnkar, Aruna; Jain, Pankaj; Paliwal, Sarvesh (Asian Journal of Pharmaceutical Research and Development, 2019)
Aerva javanica (Amaranthaceae) is a grey coloured woolly perennial tomentose shrub. Its traditional and folklore usage motivates further investigation on its pharmacognostic parameters and pharmacological potential. Therefore, in order to establish its antioxidant potential, DPPH, SOD and superoxide scavenging and total antioxidant capacity, were determined. Hydro-alcoholic extract (CE) was prepared from flowering tops of A. javanica. In order to work further on activity guided fractions, ethyl acetate (AJEAF) fraction was prepared. For in-vitro evaluation, ascorbic acid was used as standard antioxidant compound. In DPPH assay IC50 was determined as 89.00 µg/ml, as compared with standard ascorbic acid with IC50 21.80 µg/ml, with a concentration dependent scavenging of free radical. Superoxide scavenging potential in terms of SOD expressed as IC50, was determined as 61.904 µg /ml for AJEAF in contrast to 132.413 µg /ml for standard ascorbic acid. This was equivalent to 16.154 Eq SOD units /mg (EAF) per mg of sample respectively against 7.552 Eq SOD units /mg of standard. Total antioxidant capacity was found to be 283.67 mg Ascorbic acid Eq /g. Results indicated that fraction (AJEAF had significant antioxidant potential which expressed the prospective potential of fraction against metabolic disorders.